Can Sub-Saharan Africa feed itself? The role of irrigation development in the region’s drylands for food security - Xie, Hua; Pérez, Nicostrato D.; Anderson, Weston; Ringler, Claudia (Informa UK Limited, 2018)
This paper assesses the potential role of investments in irrigation in Sub-Saharan Africa in improving food security and self-sufficiency in the region. Focusing on the region’s drylands, the study identifies a potential for expanded irrigated area of 6–14 million hectares (ha), depending on technology costs and other factors. Linkage of these results with a global agricultural trade model shows that accelerated irrigation investment can effectively reduce growing food import dependency from 54% under a business-as-usual scenario to a much smaller 17–40%; and can also reduce the population at risk of hunger and child under-nutrition.